2003
DOI: 10.1097/00004770-200304000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Levels of Immunoreactive Substance P are Increased in Patients with Irreversible Pulpitis

Abstract: Odontogenic pain often involves inflammation of dental pulp tissue. Dental pulp is highly innervated with a subpopulation of sensory neurons containing neuropeptides. Substance P, released from afferent fibers (e.g. nociceptors) is associated with the development of neurogenic inflammation. In this study, we tested the hypothesis that irreversible pulpitis is associated with increased activity of peptidergic neurons, as measured by increased pulpal levels of immunoreactive substance P (iSP). We determined in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
85
0
14

Year Published

2005
2005
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(103 citation statements)
references
References 15 publications
4
85
0
14
Order By: Relevance
“…Neuropeptides are produced and released mainly by the nervous system (14,15) and also by cells other than neurocytes, e.g., macrophages (51) and eosinophils (52). CGRP and SP are abundantly copresent in nerve fibers and perivascular plexuses in the human dental pulp tissues (22,25). From the results that CGRP-and SP-positive cells in the dental pulp stroma and HPCs were also positive for 1B10 Ab (Fig.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Neuropeptides are produced and released mainly by the nervous system (14,15) and also by cells other than neurocytes, e.g., macrophages (51) and eosinophils (52). CGRP and SP are abundantly copresent in nerve fibers and perivascular plexuses in the human dental pulp tissues (22,25). From the results that CGRP-and SP-positive cells in the dental pulp stroma and HPCs were also positive for 1B10 Ab (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Both neuropeptides induce vasodilation (16), local blood flow increase (15), vascular permeability enhancement (17), and pain (18,19), thus modulating inflammation (20,21). CGRP and SP are present in pulpal and gingival tissues (17,22,23) and are increased markedly in human teeth exposing pulp due to advanced caries and/or those with painful pulpitis (24,25), which suggests a modulation of pulpal inflammation by these peptides. CGRP and SP are released from neurons by activation of proteinase-activated receptors (PAR) (14), a family of four subtypes of seven transmembrane domain receptors coupled with G protein (26).…”
mentioning
confidence: 99%
“…18 The amount of intrusive force needed for each premolar assigned to the EXPg was considered. Different reports have used a large variety of forces, ranging from 35 g to 600 g. [19][20][21] In this study, it was decided to implement 150-250 g of intrusive force. Even now, defining an orthodontic force as normal remains a paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…During this time, proinflammatory cytokine release continues, which, in some cases, could perpetuate substance P release for longer periods of time and therefore cause postbleaching symptoms in some cases. 10,11 The optical method herein used enables the recording of the number and velocity of particles conveyed by a fluid flow. 16 As red blood cells represent the vast majority of moving cells within the dental structure tooth, measurement of the Doppler-shifted, backscattered light serves as an index of PBF.…”
Section: Discussionmentioning
confidence: 99%
“…Pulp damage can trigger an inflammatory reaction that leads to the release of cell-derived factors such as adenosine triphosphate 8 neuropeptides, and prostaglandins, which excite or sensitize pulpal nociceptors. 9,10,11 This inflammatory reaction also induces vasodilatation and increased pulpal blood flow (PBF). 12,13,14 In a recent histological study, Costa et al 15 evaluated the effects of HP on pulp cells and showed notable damage to the pulp tissue, with mild inflammatory changes as well as sites of pulp necrosis in lower incisors.…”
Section: Introductionmentioning
confidence: 99%